Pengaruh Financial Literacy, Financial Attitude, dan Self-Control Terhadap Financial Well-Being pada Generasi Z di Era Digital: Studi Kasus pada Generasi Z Berpenghasilan di Kota Semarang - Adistyana Mardhyatus Sholihah; Amalia Nur Chasanah; Dwi Eko Waluyo; Fakhmi Zakaria (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Financial well-being among Generation Z, who already have income, has become an increasingly significant issue with the development of digital technology, which offers ease of transactions, but also has the potential to trigger consumptive behavior due to low levels of financial literacy, YOLO and FOMO mindsets, and high use of digital financial services. This study aims to analyze the influence of Financial Literacy, Financial Attitude, and Self-Control on the financial well-being of Generation Z, who have income in Semarang City. This study used a quantitative approach with a survey method of 100 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of the SmartPLS 4.0 program. The results show that Financial Literacy, Financial Attitude, and Self-Control have a positive and significant effect on the financial well-being of Generation Z. This study concludes that good financial literacy, the development of effective financial attitudes, and strengthening self-control in the use of digital financial services are important factors for Generation Z to achieve sustainable financial well-being.